Synchronous celiac artery and superior mesenteric artery compression syndrome: The effect of collateral circulation on the treatment procedure - Ulaş Aday; Abdullah Oguz; Hikmet Özesmer; Mehmet Veysi Bahadır (Babol University of Medical Sciences, 2023)
Background: Maintaining collateral circulation is highly important in the stenosis of celiac artery (CA), superior mesenteric artery (SMA), and inferior mesenteric artery (IMA). The SMA compression is commonly reported to be accompanied by the CA compression caused by the median arcuate ligament (MAL) while the synchronous compression of CA and SMA by other ligaments has been rarely reported. Case Presentation: In this report, we present a 64-year-old female patient who presented with a postprandial abdominal pain and weight loss. Initial evaluation indicated a synchronous compression of CA and SMA caused by MAL. The patient was planned for laparoscopic MAL division due to the presence of sufficient collateral circulation between the CA and SMA that was facilitated through the superior pancreaticoduodenal artery. Following laparoscopic release, the patient improved clinically and postoperative imaging indicated that the compression on the SMA was still present and the collateral circulation was sufficient. Conclusion: We suggest that laparoscopic MAL division can be the primary method of choice in cases with sufficient collateral circulation between the CA and SMA.